Pengaruh Literasi Zakat dan Religiusitas terhadap Kepatuhan Membayar Zakat Pertanian: Studi Kasus Kec. Pitu Riawa Kab. Sidenreng Rappang - Hikmah, Nur; Anwar, Nurfiah; Katman, Muhammad Nasri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Agriculture zakah is one of the obligations of a Muslim if their agricultural products have reached the nisab and haul. Pitu Riawa District is one of the areas with a fairly high level of paddy production. However, the realization of the collection of agricultural zakah is still very low. This study aims to determine the effect of zakah literacy and religiosity on obedience in paying zakah for agriculture communities in Pitu Riawa District, Sidenreng Rappang Regency. This research is quantitative. The research subjects were farmers in Pitu Riawa District, Sidenreng Rappang Regency, with a total sample size of 100 respondents using a purposive sampling technique. Data collection techniques using a closed-ended questionnaire The data analysis uses multiple linear regressions. The results showed that zakah literacy and religiosity had a positive and significant effect on compliance with paying zakah for agriculture in the Pitu Riawa District, Sidenreng Rappang Regency. Keywords: Zakah literacy; Religiosity; Obedience; Agriculture Zakah.